2016
DOI: 10.1007/s12028-016-0250-1
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Cognitive Deficits After Subarachnoid Hemorrhage in Rats

Abstract: Background Cognitive dysfunction can be a long-term complication following subarachnoid hemorrhage (SAH). Preclinical models have been variously characterized to emulate this disorder. This study was designed to directly compare long-term cognitive deficits in the context of similar levels of insult severity in the cisterna magna double-blood (DB) injection versus prechiasmatic blood (PB) injection SAH models. Methods Pilot work identified blood injectate volumes necessary to provide similar mortality rates (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 41 publications
2
16
0
Order By: Relevance
“…54 In another study in which both prechiasmatic blood injection and double cisternal blood injection models were compared, the authors showed significant differences between sham and SAH animals at 24 h after SAH, but failed to show any differences 7 and 35 days post-SAH. 57 Moreover, they found no significant difference in rotarod latencies in SAH animals between the two models. 57 Siler et al also failed to find significant differences between sham and SAH animals 4-6 days post-injury.…”
Section: Rotarodmentioning
confidence: 94%
See 1 more Smart Citation
“…54 In another study in which both prechiasmatic blood injection and double cisternal blood injection models were compared, the authors showed significant differences between sham and SAH animals at 24 h after SAH, but failed to show any differences 7 and 35 days post-SAH. 57 Moreover, they found no significant difference in rotarod latencies in SAH animals between the two models. 57 Siler et al also failed to find significant differences between sham and SAH animals 4-6 days post-injury.…”
Section: Rotarodmentioning
confidence: 94%
“…Because it is a less timeconsuming procedure, the Rotarod has gained popularity and its use has been more frequently reported in the SAH literature. [49][50][51][52][53][54][55][56][57] Results of all the studies using the Rotarod in SAH-induced rodents are reviewed in Supplementary Table 3.…”
Section: Rotarodmentioning
confidence: 99%
“…Several explanations, including differences in injury model (single vs. double perforation) and OFT methodological parameters, may explain this discrepancy. Differential, model-dependent effects in another anxiety-related behavioral phenotype after SAH—open arm time in the EPM—have similarly been found in rats 12, 18 .…”
Section: Discussionmentioning
confidence: 74%
“…For example, apolipoprotein E genotypes are independently associated with poor post-SAH cognitive outcomes 10, 11 . Although long-term learning and memory deficits have been demonstrated in all three primary models of SAH in rats 12–18 , most consistently in Morris water maze (MWM) testing, similar deficits have not been reported using any of the dominant methods of inducing SAH in mice. Alternate long-term emotional, social, and cognitive effects, despite their prominence in human SAH-induced cognitive impairment, have similarly not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Second, this study does not answer age‐related deficits in learning and memory similar to those seen in elderly humans, since we created disease models in intact mice and the behavioural test battery was consisted of a single open‐field test. To understand clinically relevant situations, more specific experimental settings such as experimental murine model for human senile dementia, longer neurobehavioural assessments of spatial learning ability to cause cognitive impairment, and pathological/molecular‐based preparations to validate hippocampal neuron loss should be proposed in future studies.…”
Section: Discussionmentioning
confidence: 99%